ANALISI PEMBANGUNAN KONSERVASI SUMBER DAYA AIR OLEH BADAN LINGKUNGAN HIDUP DI KOTA PEKANBARU (Studi Kasus Anak Sungai Siak) - Yuliani Pramita; Tuti Khairani Harahap (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Administration building is indispensable in making a country's development it is veryimportant for the State IndonesiaDevelopment issues of water resources conservation by environmental agency in Pekanbaru City case study tributary siak very difficult to find a solution to stop the pollution in every tributary siak that by comparing the domestic waste and environmental agency to reduce contamination of creens siak environmental agency management of the program times net (PROKASIH) one program intended to improve the water quality of the river so that meets its functions.To analyze these problems the author uses the theory of Thompson, which corresponds to these problems the administration building is the organization's ability to